1D Triboelectric Nanogenerator Operating by Repeatedly Stretching and as a Self‐Powered Electronic Fence and Geological Monitor. Issue 2 (17th January 2020) - Yang, Jing; Yang, Shuai; Guo, Rui; Li, Yanping; Sang, Shengbo; Zhang, Hulin
Abstract: The micromechanical energy caused by a repeating tension is abundant and widely existed in human life, which is usually related to dynamic monitoring in a low‐dimensional system. Here, a 1D tensile triboelectric nanogenerator (TENG) that is consisted of a copper and a latex tube is reported. The subtle TENG can not only serve as a sustainable power source by harvesting tensile mechanical energy, but also operate actively to detect some surrounding mechanical stimulations. Due to the high sensitivity to stretching, the TENG unit shows a self‐powered counting function. Furthermore, a sensor square frame, composed of four TENG units, is demonstrated as a feasible self‐powered electronic fence by effectively monitoring ambient collisions from different directions. In addition, the simulated landslide experiment indicates that the tensile TENG can detect different geological activities and has a directional selectivity that facilitates geological hazard monitoring. This work further expands TENG‐based applications, especially in safety engineering and geological monitoring. Abstract : A 1D tensile triboelectric nanogenerator (TENG) is demonstrated to actively detect some surrounding mechanical stimulations. Due to the high sensitivity to stretching, a feasible self‐powered electronic fence is fabricated to monitor ambient collisions. Besides, the tensile TENG shows a capacity of detecting different geological activities and having a directional selectivity that facilitates geological hazard monitoring.